Prediction of macroscopic damage behaviour of precipitation strengthened steels via multiscale simulations. Issue 2 (September 2015) - Molnar, D.; Weber, U.; Binkele, P.; Rapp, D.; Schmauder, S.
Abstract A multiscale modelling approach is presented that sequentially connects in total five simulation methods via parameter transfers in order to capture the macroscopic damage behaviour due to an underlying nano structure of copper precipitates in bcc iron. In this multiscale approach, information on precipitation states is taken from kinetic Monte‐Carlo and Phasefield simulations as well as from experimental data. Based on a calibration of Dislocation Dynamics by Molecular Dynamics simulations as well as on testing conditions known from experiments, Dislocation Dynamics simulations with an infinite dislocation on a single glide plane provide strengthening levels which are related to a reference stress‐strain curve obtained from experiments. Subsequently, the macroscopic damage behaviour is simulated with the Finite‐Element‐Method including the Rousselier Damage Model for the reference state as well as for the virtually aged states. The results are validated by comparison with experimental results and predictions are made with respect to specific precipitation cases. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)